Understanding Iran [ - Green, Jerrold D.; Wehrey, Frederic M.; Wolf, Charles , 1924- (RAND Corporation monograph series, 2009)
"Over the years, there have been numerous efforts to locate the roots of the Islamic Republic's intentions and motivations in the distinctiveness of its political culture and history. A rich and ancient nation, Iran has always beguiled outsiders. This complexity, combined with America's lack of access to Iran since 1979, has produced a peculiar view of the Islamic Republic, a view defined by mystique and a superficial reading that places too much emphasis on Iran's 'abnormal' and 'exceptional' characteristics. This document is a short, accessible guide intended to help U.S. policymakers understand the Islamic Republic. It offers a set of short analytic observations about the processes, institutions, networks, and actors that define Iran's politics, strategy, economic policy, and diplomacy. From these, it sets out an argument for appreciating the challenges and fundamentals of negotiating with Iran."--Summary, p. ix.